Obtenção de extrato de café para aplicação como antioxidante natural em linguiça toscana - Fetsch, Vanessa Tanara (2021)
Meat products are highly susceptible to oxidation, industrially controlled by synthetic antioxidants. Due to the growing interest of consumers for healthier foods, the demand for natural alternatives is increasing. Coffee is rich in antioxidant compounds, which makes it a possible option to use synthetic antioxidants. This study aimed to evaluate the efficiency of coffee extracts as a natural antioxidant in Tuscan sausage. Initially, the use of extraction by shaking in a shaker and assisted by ultrasound (bath and indirect probe) at different temperatures (30 to 80 °C) using water and 30% ethanol solution as solvent was evaluated. Higher antioxidant activity values were obtained in an ultrasound bath at 70 °C using 30% ethanol solution (p < 0.05). Subsequently, a Central Composite Rotational Design 23 was used with the independent variables: (x1) extraction time (1.6 to 18.4 min); (x2) ethanol/water ratio (21.6 to 38.4% ethanol); and (x3) sample/solvent ratio (g ml-1 ) (1.6/100 to 18.4/100). The tests were carried out in an ultrasound bath at 70 °C. The response variables studied were the levels of dark compounds, total phenolics, chlorogenic acids, caffeoylquinic acid and caffeine, in addition to the antioxidant activity by the DPPH and ABTS+• methods. Except for the DPPH, valid models (p ≤ 0.05) were obtained, with a coefficient of determination > 0.751. It was found that a higher content of bioactives and, consequently, a higher antioxidant activity, can be obtained in the central point region with optimization of responses under the conditions of 14.2 min, ethanol/water ratio of 34.2% and ratio sample/solvent (g ml-1 ) of 5.8/100. Using central point and optimized parameters, Coffea canephora and Coffea arabica (green and medium roast) were characterized in order to evaluate which ones presented extracts with higher contents of bioactives and antioxidant capacity. The extracts with the highest antioxidant activity, in the parameters used, were the green and roasted Coffea canephora species, which were dried in a spray dryer and applied to a standard formulation of Tuscan sausage at two concentrations, 0.32 and 1%, and compared to one sample with sodium erythorbate antioxidant. These samples were evaluated for approximate composition and microbiological quality required by law. At times 0, 10, 20 and 30 days, instrumental color measurement, texture profile analysis (TPA), metmyoglobin formation and lipid oxidation of the samples were evaluated. The parameters color, TPA and metmyoglobin formation did not show significant changes (p ≤ 0.05) over time for any of the samples, while for the formation of malonaldehyde, there was only a significant increase at the end of the shelf life of samples, being superior for the samples with 0.32% coffee extract. In the sensory evaluation of the hedonic scale, the sample with 0.32% green coffee proved an acceptance like the standard, while the others were significantly less accepted, but with the exception of the sample with 1% roasted coffee extract, the others had scores above 7 on a 9-point scale. Finally, coffee extract was found to be a great substitute as an antioxidant for Tuscan sausage and possibly other meat products.